Thermal shock resistance of alumina ceramics enhanced by nanostructured conformal coatings using metal–organic frameworks. (1st July 2016) - Su, Honghong; Hou, Guohui; Cheng, Zhiqiang; Xia, Biao; Fang, Xufei; Yan, Bo; Feng, Xue
Abstract: In this article we provide a large-scale and low-cost method, based on metal–organic frameworks, to fabricate nanostructured conformal coatings with the same material as the substrate. Such design can reduce the thermal mismatch between coatings and substrate and massively change the local thermal conductivity and interfacial heat transfer coefficient. Therefore, the thermal shock resistance can be enhanced to about 75%. We describe all aspects of such nanostructured conformal coatings from fabrication to characterization. Moreover, the mechanism of this enhancement due to high porosity and low pore size of nanoporous coating is discussed.